Interspeech 2014 2014
DOI: 10.21437/interspeech.2014-244
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age in the production of European Portuguese vowels

Abstract: The elderly population is quickly increasing in the developed countries. However, in European Portuguese (EP) no studies have examined the impact of age-related structural changes in speech acoustics. The purpose of this paper is to analyse the effect of age ([60-70], [71-80] and [81-90]), gender and type of vowel in the acoustic characteristics (fundamental frequency (F0), first formant (F1), second formant (F2) and duration) of the EP vowels. A sample of 78 speakers was selected from the database of elderly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…The increase of the TH is in accordance with our previous acoustic study [16] of aging speech for EP. In other words, the tongue raising (higher TH) is correlated with a decrease in F1 [9,56], which has been reported for both EP [15,16] and other languages [4,5,44,77,78] with aging. However, Pellegrini et al [17] reported higher F1 values for vowels produced by older EP females.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…The increase of the TH is in accordance with our previous acoustic study [16] of aging speech for EP. In other words, the tongue raising (higher TH) is correlated with a decrease in F1 [9,56], which has been reported for both EP [15,16] and other languages [4,5,44,77,78] with aging. However, Pellegrini et al [17] reported higher F1 values for vowels produced by older EP females.…”
Section: Discussionmentioning
confidence: 73%
“…As for age-related changes on vowel formant frequencies (mostly F1 and F2), the results across studies are highly inconsistent [4,5,11,14]. In addition, European Portuguese (EP) vowels presented a different pattern of formant frequencies variation with age and gender [15][16][17]. Albuquerque et al [16,18] observed that vowel formants tend to decrease mainly in females and to centralize in males with aging, and these changes might be related to specific articulatory adjustments of the older speakers during speech.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Concerning European Portuguese (EP), there are only a few studies regarding age-related speech variations, mainly, at the segmental level (Albuquerque, Oliveira, Teixeira, Sa-Couto, & Figueiredo, 2019;Albuquerque et al, 2014;Guimarães & Abberton, 2005;Pellegrini et al, 2013). Still, vowel production in reading tasks failed to provide a clear picture of the age effects in spontaneous speech and has some limitations.…”
Section: Introductionmentioning
confidence: 99%
“…Since there is a paucity of literature on EP speech acoustics and the available data were collected from a small number of speakers (Albuquerque et al, 2014;Escudero, Boersma, Rauber, & Bion, 2009;Martins, 1973;Oliveira, Cunha, Silva, Teixeira, & Sa-Couto, 2012), this study also provides valuable insights to understand the aging effects on natural spoken language production. Knowledge of how speech changes with age is essential for the development of automatic speech recognition (ASR) systems suitable for older voices (i.e., personalized reading aids and voice prostheses) (Vipperla, Renals, & Frankel, 2010), for clinical assessment and treatment of different speech disorders that are often age-related, and to provide information for other fields of knowledge (i.e., phonetics, speech science, forensic linguistics and biometric recognition).…”
Section: Introductionmentioning
confidence: 99%